Public Private Partnerships Review of Kazakhstan - Ruiz Rivadeneira, Ana Maria (OECD Publishing, 2019)
Kazakhstan has put in place a well-structured legal and institutional framework for preparing Public Private Partnerships (PPPs) at both the national and regional levels. The government has prioritised PPPs as a delivery mode for both economic and social infrastructure. The central emphasis on PPPs had a strong impact at the regional level with a large number of relatively small projects signed in the past years. At the national level the impact has been modest mostly due to financing challenges. In terms of priority areas for reform, the report outlines capacity building (particularly during the project preparation phase), the need to promote quality over quantity of PPPs, strengthening the methods used to guide the choice of delivery mode, and transparency and accounting of contingent liabilities